Morphological characters and dry mass production in winter tomato as affected by foliar application of plant growth regulators (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
A field experiment was conducted at the field laboratory of Crop Botany Department, Bangladesh Agricultural University, Mymensingh to study the effect of different levels of plant growth regulators, PGRs (GA3, NAA) on the growth and yield in two tomato varieties. The experiment was laid out in a three factorial randomized completely block design ( RCBD) with  16 treatments viz. 2 varieties (Ratan and Roma V.F.) × 2 PGRs (GA3, NAA) × 4 concentration levels of PGRs ( 0, 25, 50 and 100 ppm). The result showed that tomato variety Ratan produced higher yield (3.92 kg plant−1) by increasing plant height, stem diameter at base, branch plant−1, leaves plant−1, fresh and dry weight of leaves,  number of flowers plant−1 than the variety Roma V.F. (3.71 kg plant−1). PGRs enhanced plant height, number of leaves plant−1, fresh and dry weight of leaves, etc. A higher yield was observed in plants treated with GA3 (4.07 kg plant−1) than in the plants treated with NAA (3.55 kg plant−1). Among the concentrations of PGRs, 50 ppm exhibited better performances producing higher yield (5.02 kg plant−1). Interaction effects of variety, PGR and concentration showed that higher yield (5.06 kg plant−1) was derived from the variety Ratan when treated with 50 ppm of GA3.Asian Australas. J. Biosci. Biotechnol. 2016, 1 (3), 514-520